The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/agg2.20201
|View full text |Cite
|
Sign up to set email alerts
|

Do crops' responses to sulfur vary with its forms?

Abstract: The most common formsof S fertilizers in the northern Great Plains are ammonium sulfate (AS), ammonium thiosulfate (ATS), and elemental S (ES). Among these, AS is preferred over the others because of its readily available SO 4 2form, and it can be blended with other dry fertilizer granules, but SO 4 2is prone to leaching. Recently, fertilizer industries introduced micronized (<100 μm) S (MS) fertilizer formulations to hope that the smaller elemental S particles would increase the rate of S oxidation. Across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Studies that examine the extent and magnitude of crop response to S fertilization (e.g., Brooks et al., 2022; de Borja Reis et al., 2021; Goyal et al., 2021) should consider the application of granular P fertilizers prior to the crop being studied as a possible factor obviating the need for, or reducing crop response to, direct S fertilization. Dismissing the potential contribution of P fertilizers to satisfy the S needs of crops, seems unwise given that when applied at a rate to replace grain P removal of both crops in a corn and soybean rotation, the P fertilizers can supply 50% or more of grain S removal of the subsequent crop.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that examine the extent and magnitude of crop response to S fertilization (e.g., Brooks et al., 2022; de Borja Reis et al., 2021; Goyal et al., 2021) should consider the application of granular P fertilizers prior to the crop being studied as a possible factor obviating the need for, or reducing crop response to, direct S fertilization. Dismissing the potential contribution of P fertilizers to satisfy the S needs of crops, seems unwise given that when applied at a rate to replace grain P removal of both crops in a corn and soybean rotation, the P fertilizers can supply 50% or more of grain S removal of the subsequent crop.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, elemental S accounted for half of the S application, which was also a significant factor contributing to the reduced SUE. To accelerate the rate of elemental S oxidation, the use of elemental S with a smaller particle size or inoculated with S-oxidizing bacteria has gained broad attention [56,65,66]. The application of elemental S combined with organic amendments such as poultry and farmyard manure could also increase S oxidation and availability due to improved microbial activity [34].…”
Section: Discussionmentioning
confidence: 99%
“…Soil extractable S, the most routinely measured diagnostic test in farmer fields in the Midwest, has not been a reliable indicator of S deficiency because of the complex biotic and abiotic factors that govern S mineralization (Dick et al., 2008; Kaur et al., 2019; Pagani & Echeverria, 2011). Studies from North Dakota reported that no soil factors, including SOM and Mehlich‐3 extractable S were good indicators of yield response following S application (Franzen & Grant, 2015; Goyal et al., 2021). In Minnesota, a negative correlation between soybean yield and soil S was reported (Kaiser & Kim, 2013).…”
Section: Introductionmentioning
confidence: 99%